2015
DOI: 10.1021/acsinfecdis.5b00090
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies That Recognize the Alkylation Signature of Antimalarial Ozonides OZ277 (Arterolane) and OZ439 (Artefenomel)

Abstract: The singular structure of artemisinin, with its embedded 1,2,4-trioxane heterocycle, has inspired the discovery of numerous semisynthetic artemisinin and structurally diverse synthetic peroxide antimalarials, including ozonides OZ277 (arterolane) and OZ439 (artefenomel). Despite the critical importance of artemisinin combination therapies (ACTs), the precise mode of action of peroxidic antimalarials is not fully understood. However, it has long been proposed that the peroxide bond in artemisinin and other anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…Four peaks at m / z 782.3 were detected which were assigned to the four possible regioisomers of alkylated heme adduct 648 as reported for heme–artemisinin adducts [ 558 ]. Later, in an initial study dealing with monoclonal antibodies that recognize the alkylation signature (sum of heme and protein alkylation) of synthetic peroxides it was shown that the artemisinins alkylate proteins in P. falciparum [ 559 ].…”
Section: Reviewmentioning
confidence: 99%
“…Four peaks at m / z 782.3 were detected which were assigned to the four possible regioisomers of alkylated heme adduct 648 as reported for heme–artemisinin adducts [ 558 ]. Later, in an initial study dealing with monoclonal antibodies that recognize the alkylation signature (sum of heme and protein alkylation) of synthetic peroxides it was shown that the artemisinins alkylate proteins in P. falciparum [ 559 ].…”
Section: Reviewmentioning
confidence: 99%
“…It has been proposed that, like artemisinin, the antimalarial synthetic peroxides also undergo reductive cleavage by the ferrous heme of the catabolized hemoglobin [ 113 ]. This peroxide reduction resulted in active carbon-centered radicals that alkylate heme and the parasite proteins [ 113 ].…”
Section: Artemisinin Inspired Novel Antimalarial Compoundsmentioning
confidence: 99%
“…Since the structural analogies between artemisinins and ozonides (Fig. 1 ) suggest that they share similar modes of action, and thus some level of cross resistance [ 9 , 10 , 51 , 52 ], the per cent survival of an artemisinin-resistant clinical isolate (Cam3.I R539T ) treated with DHA, OZ277, OZ439, and four additional next-generation ozonides (Fig. 1 ) using the RSA 0–3h as described by Witkowski et al [ 48 , 49 ] was evaluated.…”
Section: Introductionmentioning
confidence: 99%